PENGARUH DIABETES SELF CARE MANAGEMENT EDUCATION TERHADAP PENGETAHUAN PENDERITA DIABETES MELITUS TIPE 2 DI WILAYAH KERJA PUSKESMAS PARIAMAN - ANDRIANI, LINDA; PRASETYANINGSIH, PRASETYANINGSIH; KASMORA, DEPERMAN; SAPUTRA, RIZKI RAMADHAN (As-Shiha : JOURNAL OF MEDICAL RESEARCH, 2024)
Diabetes mellitus (DM) is now growing into a global health problem, its prevalence in 2019 was 371 million cases and is predicted to increase by 55 percent to 592 million in 2035. The purpose of the study was to determine the effect of diabetes self-care management education on the knowledge of Type 2 Diabetes Mellitus sufferers in the Pariaman Health Center Work Area, Pariaman City. The type of quasi-experimental research with one group pretest posttest design. Sampling was carried out using the total sampling technique, namely 36 respondents. The data collection tool used was a questionnaire filled in by the researcher and data processing was carried out using a computerized system. The results showed that most of the respondents (61.1%) had a low level of knowledge before being given diabetes self-care management education. Almost all respondents (86.1%) experienced an increase in their knowledge after being given diabetes self-care management education. Statistical analysis showed that there was an effect of diabetes self-care management education on increasing knowledge in type 2 diabetes mellitus sufferers in the Pariaman Health Center Work Area (p-value = 0.000 <0.05). In conclusion, providing diabetes self-care management education increases the knowledge of type 2 diabetes mellitus sufferers in the Pariaman Health Center Work Area.